Utility of bilateral superficial cervical plexus block in thyroidectomy patients for post-operative analgesia - Shah, Parth M.; Kheskani, Divya N. (International Journal of Research in Medical Sciences, 2021)
Background: Thyroidectomy is painful procedure hence multimodal analgesia is required. Superficial cervical plexus block can be used for analgesia in thyroid surgeries. USG guided cervical plexus block administration is safe and latest technique as a part of multimodal analgesia for thyroid surgery. Methods: After obtaining consent 60 ASA grade I-II adult patients undergoing elective thyroid surgery were included and randomly divided into two groups (group B)-0.25% bupivacaine and (group S)-normal saline. Induction and maintenance under general anesthesia carried out as per standard protocol. After Induction USG guided block was administered with the drug solution as per allocated group. After surgery, patients were extubated and shifted to recovery room. Vital parameters were monitored. Patients were asked about their pain based on the 11-point numerical rating scales (NRS) score. The NRS score and other variables were documented at 3rd hour, 6th hour, 12th hour, and 24th hour at wards after the end of surgery. Time since the end of surgery to the first analgesia request was documented together with total analgesia consumed in the first 24 hours. If NRS score was ≥4 inj. Tramadol iv in incremental doses of 25 mg was given until pain relieved. Results: Time to first dose of analgesia was higher in group B compared to group S. Total analgesic dose of tramadol during first 24 hours was lower in group B compared to group S Conclusions: bilateral superficial cervical plexus block can be used as a part of multi-modal analgesia in patients of thyroidectoy.